Dynamics of survival of motor neuron (SMN) protein interaction with the mRNA‐binding protein IMP1 facilitates its trafficking into motor neuron axons. Issue 3 (4th October 2013) - Fallini, Claudia; Rouanet, Jeremy P.; Donlin‐Asp, Paul G.; Guo, Peng; Zhang, Honglai; Singer, Robert H.; Rossoll, Wilfried; Bassell, Gary J.; Sotelo‐Silveira, José R.; Holt, Christine E.
ABSTRACT Spinal muscular atrophy (SMA) is a lethal neurodegenerative disease specifically affecting spinal motor neurons. SMA is caused by the homozygous deletion or mutation of the survival of motor neuron 1 (SMN1) gene. The SMN protein plays an essential role in the assembly of spliceosomal ribonucleoproteins. However, it is still unclear how low levels of the ubiquitously expressed SMN protein lead to the selective degeneration of motor neurons. An additional role for SMN in the regulation of the axonal transport of mRNA‐binding proteins (mRBPs) and their target mRNAs has been proposed. Indeed, several mRBPs have been shown to interact with SMN, and the axonal levels of few mRNAs, such as the β‐actin mRNA, are reduced in SMA motor neurons. In this study we have identified the β‐actin mRNA‐binding protein IMP1/ZBP1 as a novel SMN‐interacting protein. Using a combination of biochemical assays and quantitative imaging techniques in primary motor neurons, we show that IMP1 associates with SMN in individual granules that are actively transported in motor neuron axons. Furthermore, we demonstrate that IMP1 axonal localization depends on SMN levels, and that SMN deficiency in SMA motor neurons leads to a dramatic reduction of IMP1 protein levels. In contrast, no difference in IMP1 protein levels was detected in whole brain lysates from SMA mice, further suggesting neuron specific roles of SMN in IMP1 expression and localization. Taken together, our data support a role for SMN in the regulation of mRNA localization and axonal transport through its interaction with mRBPs such as IMP1. © 2013 Wiley Periodicals, Inc. Develop Neurobiol 74: 319–332, 2014